Association of Medicaid Expansion With Cancer Stage and Disparities in Newly Diagnosed Young Adults. (21st May 2021) - Ji, Xu; Castellino, Sharon M; Mertens, Ann C; Zhao, Jingxuan; Nogueira, Leticia; Jemal, Ahmedin; Yabroff, K Robin; Han, Xuesong
Abstract: Background: Young adults (YAs) experience higher uninsurance rates and more advanced stage at cancer diagnosis than older counterparts. We examined the association of the Affordable Care Act Medicaid expansion with insurance coverage and stage at diagnosis among YAs newly diagnosed with cancer. Methods: Using the National Cancer Database, we identified 309 413 YAs aged 18-39 years who received a first cancer diagnosis in 2011-2016. Outcomes included percentages of YAs without health insurance at diagnosis, with stage I (early-stage) diagnoses, and with stage IV (advanced-stage) diagnoses. We conducted difference-in-difference (DD) analyses to examine outcomes before and after states implemented Medicaid expansion compared with nonexpansion states. All statistical tests were 2-sided. Results: The percentage of uninsured YAs decreased more in expansion than nonexpansion states (adjusted DD = −1.0 percentage points [ppt], 95% confidence interval [CI] = −1.4 to −0.7 ppt, P  <   .001). The overall percentage of stage I diagnoses increased (adjusted DD = 1.4 ppt, 95% CI = 0.6 to 2.2 ppt, P  <   .001) in expansion compared with nonexpansion states, with greater improvement among YAs in rural areas (adjusted DD = 7.2 ppt, 95% CI = 0.2 to 14.3 ppt, P  =   .045) than metropolitan areas (adjusted DD = 1.3 ppt, 95% CI = 0.4 to 2.2 ppt, P  =   .004) and among non-Hispanic Black patients (adjusted DD = 2.2 ppt, 95% CI = −0.03 to 4.4 ppt, P  =   .05) than non-Hispanic White patients (adjusted DD = 1.4 ppt, 95% CI = 0.4 to 2.3 ppt, P  =   .008). Despite the non-statistically significant change in stage IV diagnoses overall, the percentage declined more (adjusted DD = −1.2 ppt, 95% CI = −2.2 to −0.2 ppt, P  =   .02) among melanoma patients in expansion relative to nonexpansion states. Conclusions: We provide the first evidence, to our knowledge, on the association of Medicaid expansion with shifts to early-stage cancer at diagnosis and a narrowing of rural-urban and Black-White disparities in YA cancer patients.